(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In recent years graph theory has established itself as an important mathematical tool in a wide variety of subjects, ranging from operational research, chemistry to genetics and linguistics, electrical engineering ,geography to sociology, computer science and architecture. The field graph theory started its journey from the problem of Königsberg Bridge in 1735. This paper gives an overview of the applications of graph theory in heterogeneous fields to some extent.